Long-term disability trajectories in relapsing multiple sclerosis patients treated with early intensive or escalation treatment strategies - Iaffaldano, Pietro; Lucisano, Giuseppe; Caputo, Francesca; Paolicelli, Damiano; Patti, Francesco; Zaffaroni, Mauro; Brescia Morra, Vincenzo; Pozzilli, Carlo; De Luca, Giovanna; Inglese, Matilde; Salemi, Giuseppe; Maniscalco, Giorgia Teresa; et al. (Therapeutic advances in neurological disorders, 2021)
Background and aims: No consensus exists on how aggressively to treat relapsing–remitting multiple sclerosis (RRMS) nor on the timing of the treatment. The objective of this study was to evaluate disability trajectories in RRMS patients treated with an early intensive treatment (EIT) or with a moderate-efficacy treatment followed by escalation to higher-efficacy disease modifying therapy (ESC). Methods: RRMS patients with ⩾5-year follow-up and ⩾3 visits after disease modifying therapy (DMT) start were selected from the Italian MS Registry. EIT group included patients who received as first DMT fingolimod, natalizumab, mitoxantrone, alemtuzumab, ocrelizumab, cladribine. ESC group patients received the high efficacy DMT after ⩾1 year of glatiramer acetate, interferons, azathioprine, teriflunomide or dimethylfumarate treatment. Patients were 1:1 propensity score (PS) matched for characteristics at the first DMT. The disability trajectories were evaluated by applying a longitudinal model for repeated measures. The effect of early versus late start of high-efficacy DMT was assessed by the mean annual Expanded Disability Status Scale (EDSS) changes compared with baseline values (delta-EDSS) in EIT and ESC groups. Results: The study cohort included 2702 RRMS patients. The PS matching procedure produced 363 pairs, followed for a median (interquartile range) of 8.5 (6.5–11.7) years. Mean annual delta-EDSS values were all significantly (p < 0.02) higher in the ESC group compared with the EIT group. In particular, the mean delta-EDSS differences between the two groups tended to increase from 0.1 (0.01–0.19, p = 0.03) at 1 year to 0.30 (0.07–0.53, p = 0.009) at 5 years and to 0.67 (0.31–1.03, p = 0.0003) at 10 years. Conclusion: Our results indicate that EIT strategy is more effective than ESC strategy in controlling disability progression over time.